EVALUATION OF PENETRATION TESTING ON WPA2-ENABLED WLAN NETWORK VULNERABILITIES - Nizam (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2025)
The rapid development of wireless technology provides convenience in accessing information, yet also raises significant challenges related to network security. This research aims to analyze the vulnerability level of Wireless Local Area Network (WLAN) by applying the penetration testing method. The study focuses on the WPA2 security protocol, with two main attack scenarios: Cracking the Encryption and Man in the Middle Attack (MITM). The methodology involves several stages, including network monitoring, packet capture, deauthentication attack, and encryption key cracking using Aircrack-ng. Additionally, a MITM attack simulation was carried out using Ettercap through ARP poisoning techniques to intercept network communications. The results indicate that the encryption cracking attempt on the target SSID failed due to wordlist limitations, while the MITM simulation successfully intercepted sensitive data on an open network. Based on the findings, it can be concluded that although WPA2 offers stronger protection compared to previous encryption methods, vulnerability potentials still exist and can be exploited at the application layer if insecure communication protocols like HTTP are utilized.